Nucleation Kinetics of Carbamazepine-Saccharin (CBZ-SAC) Co-Crystal - Khairool Azizul, Mohammad; Syarifah, Abd Rahim; Mohd Rushdi, Abu Bakar (2014)
In this study the effect of the heating/cooling rate of various CBZ-SAC mixture in ethanol was investigated in order to deduce the metastable zone width (MSZW) and the nucleation order. Nivlt' s equation involving the maximum temperature difference ATm between dissolution and crystallization temperatures of CBZ-SAC co-crystals with the heating/cooling rate r was applied for the study of nucleation kinetics by the polythermal method. A step towards the determination of dissolution temperature of the crystals has been improved. The results showed that dissolution temperature for CBZ-SAC co-crystal mixture increased with the increase in heating rate, CBZ-concentration and the ratio of SAC to CBZ in ethanol solution. The analysis revealed that a nucleation order for CBZ-SAC co-crystals increases with the SAC to CBZ ratio and is in the range of 1.58 to 6.31.